Application of tight-binding method to calculate the band structure and the effect of pressure in crystal ZnSe - Hussein Sultan; Mumtaz Hussien (College of Education for Pure Sciences, 2021)
Abstract In this research tight-binding method has been applied to calculate the band structure in ZnSe crystal, the matrix elements of have been calculated using the method used by Vogl and Cohen. A computer program has been designed in MATLAB language to calculate the band structure in the ZnSe crystal, a sample of points has been formed in the first Brillouin zone (reduced zone) between the high symmetry points (L →Γ,Γ→X→(U,K) →Γ) . The energy eigen values is calculated along the high symmetry paths, the obtained results have been compared with previous works of Vogl and Cohen which shows a good agreements. A comparison between the ZnSe band structure based on sp3 and sp3s* models has been done and the energy gap between the conduction and valence bands at the high symmetry points is calculated for the sp3s*. The effect of pressure on the ZnSe band structure is calculated in the range (10-40) Gpa by calculating the matrix element under different pressure, the results show broadening in band gap due to applied pressure, the conduction band is shifted toward the high energy while the valence band is shifted toward the lower energy. The band gap is calculated values for high symmetric points were determined with pressure change and compared with theoretical calculations.